COMMON FABRICS FOR SEWING pocket guide : a glossary of fabrics and how to use them for sewing projects. (Rocky Nook, 2023)
Quickly learn the basics of the many different kinds of fabrics commonly used for sewing projects so you can pick the perfect material for your project! Designed for sewists and DIY crafters who need a guide to the many common fabrics used for sewing. This handy and ultra-portable quick reference Pocket Guide offers sewists information on over 50 types of fabrics, what types of garments they're commonly used for, and tips for how to sew with them • Learn the difference between natural and synthetic fabrics • Discover the intricacies of how fabric is woven--and how that effects the way the fabric is sewed • Understand terms like nap, weft, and weave, all words that describe how a fabric handles • Tips for placing pattern pieces and cutting fabric • A glossary of over 50 fabrics with information on their common uses and tips for sewing with them.